Implementation of Language Literacy Learning in Group A of PAUD Al-Kautsar Cilegon Banten - Nelly Aulia Rosmawati; Ratih Kusumawardani; Laily Rosidah (Universitas Negeri Makassar, 2023)
Language literacy or pre-literacy in early childhood is the ability to read and write and analyze, respond, and use language that can be applied through reading corners, drawing activities, and a culture of reading at home in collaboration between parents and schools. This study aims to determine the application of literacy learning and the methods and media applied to literacy learning in group A of PAUD Al-Kautsar Cilegon. This research uses descriptive qualitative research. Data collection used in this research is observation, interview, and documentation. The results showed that the application of language literacy learning in group A of PAUD Al-Kautsar Cilegon looks quite optimal in its application by the literacy program that should be, starting from the arrangement of classes and environments rich in literacy as well as facilities provided by schools such as reading corners and in its application children are not taught directly to read and write but are introduced to reading and writing with habituation activities that have been designed by the school, and in its application there are several learning methods and various learning media that support the application of literacy learning.